Anglican against Puritan: Ideological Origins during the Marian Exile - Molen, Ronald J. Vander (Church history, 1973)
Traditionally, divisions among Protestant groups during the English Reformation have been examined as deep theological crises, simply written off as manifestations of economic or political struggles, or, more recently, treated as having roots in basic ideological commitments. One of the most important Protestant divisions, that between Anglicans and Puritans, has undoubtedly had a great impact on western history; however, it lacks full treatment from the point of view of its intellectual and social bases. One's attention is easily drawn to the Anglican-Puritan conflict of Queen Elizabeth's rule or to the seventeenth-century revolution in England; but earlier origins often receive only cursory treatment. Actually, the ideas, party divisions and social characteristics of the Anglican-Puritan division in the Elizabethan and Stuart eras have their roots and first appearance during the flight of Protestants from England after the reign of King Edward VI. It is to the ideological and social factors which appeared in the congregation of English exiles at Frankfurt-am-Main in 1554–55 that I should like to draw attention, for it was in the “Troubles at Frankfurt” that the historical pattern of the Anglican-Puritan division assumed a form which was to have such a great impact on western society.